Studi Komparatif Manajemen Pendidikan Islam dan Manajemen Penddikan Barat - Minggusta Juliadarma (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
The purpose of this research is to elaborate comprehensively about the differences that can be explored from Islamic education management and western education management. This study uses a library research method with documentation study as a data collection technique. The results showed that there were at least five substantial differences between Islamic education management and western education management. The difference lies in the purpose of education, basic education, curriculum management, student management, and management of educational institutions.